(Nie)krótka historia "Filologii Polskiej" i kilka uwag o roczniku. Pięćdziesiąt lat polonistyki akademickiej w Zielonej Górze (1971-2021) = (Un)short history of "Filologia Polska" and some remarks on the yearbook - Sztyber, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The sketch is an attempt to present "Filologia Polska. Roczniki Naukowe Uniwersytetu Zielonogórskiego" [Polish Philology. Zielona Góra University Research Yearbook]. The journal originated in 2015 as a continuation of two former publishing series initiated by Wyższa Szkoła Pedagogiczna [Higher Pedagogical School] (1975-1999) and University of Zielona Góra (2003-2013). Fifteen volumes have been printed since 1975 (up to 2013) marked with a similar (sub)title - "Filologia Polska". The yearly was founded with new requirements regime stating i.a. a website, double blind review process, indexing within external (national or foreign) databases.
Keywords: "Filologia Polska"; rocznik; czasopisma naukowe; Uniwersytet Zielonogórski; yearbook; scientific journals; University of Zielona Góra